Implementasi Family Development Session Program Keluarga Harapan - Evan Notatema Hia; Matias Siagian; Nurman Achmad (Universitas Medan Area, 2021)
This study aims to determine the implementation of the Family Development Session of the family hope program in the Kelurahan Pekan Selesai, Selesai Subdistrict, Langkat Regency of North Sumatra. This type of research uses a qualitative descriptive approach, data collection methods in the form of observation, documentation and interviews with the informants who have been determined. The results of this study indicate that the implementing agencies of the PKH Social and HR Service have carried out socialization about FDS at the district, sub-district, sub-district level and to beneficiaries, the existence of social assistants in implementing problem identification using the MPA technique (participatory assessment method) to recipients. Furthermore, the material learning stage shows that the compliance of the social facilitator has also implemented the FDS module learning, but there are still obstacles to the use of teaching material components for beneficiaries. The reporting stage shows that the social facilitator has complied with reporting on FDS implementation activities every month either manually by collecting hard copies or reports based on the E-PKH application.